Risk factors for developing dementia in type 2 diabetes mellitus patients with mild cognitive impairment - Albai O (Dove Medical Press, 2019)
Oana Albai,1 Mirela Frandes,2 Romulus Timar,1 Deiana Roman,3 Bogdan Timar2 1Second Department of Internal Medicine, “Victor Babes” University of Medicine and Pharmacy, Timisoara, Romania; 2Department of Functional Sciences, “Victor Babes” University of Medicine and Pharmacy, Timisoara, Romania; 3Municipal Clinical Emergency Hospital, Timisoara, Romania Background: Dementia and cognitive dysfunction have many causes. There is strong evidence that diabetes mellitus (DM) increases the risk of cognitive impairment and dementia. Optimal glycemic control, identification of diabetic risk factors, and prophylactic approach are essential in the prevention of cognitive complications.Aims: The main purpose of this study was to establish the cognitive impairment in DM patients, cared for in the Diabetes Center from Timisoara. Also, we investigated the prevalence of dementia in our group as well as the risk factors involved in the progression of mild cognitive impairment (MCI) to dementia.Patients and methods: We considered a sample of 207 type 2 DM (T2DM) patients, aged between 33 and 81 years, mean 57.49 (±11.37) years. We established the diagnosis of dementia based on the Mini-Mental State Examination (MMSE) test, as well as on the psychological testing, psychiatric and neurological investigations, and imaging tests (computerized tomography and MRI).Results: A percentage of 42.03% of patients presented MCI, mean age 63 (57.00–71.00) years, being older than patients without MCI, mean age 52.00 (45.00–61.00) years, P<0.001. We observed that diabetes duration was a significant risk factor for developing dementia. Also, patients with MCI presented higher values of body fat than patients without MCI. Moreover, we found that glucose levels, low-density lipoprotein cholesterol levels, the presence of stroke events, and the presence of cardiovascular disease were significant risk factors for MCI conversion to dementia.Conclusion: Patients with T2DM at early to severe stages of MCI are more likely to develop dementia and should be regularly evaluated for their cognitive status. Regular administrations of the MMSE test can be done to detect early stages of MCI development. Also, to reduce the progression of cognitive impairment to dementia, it is worthwhile to give greater importance to glycemic control and overall DM management. Keywords: diabetes mellitus, metabolic syndrome, insulin resistance, cognitive impairment, dementia